Symbolic accountability and the corruption control crisis in Indonesian villages - Nina Yusnita Yamin; Haryono Pasang Kamase; Selmita Paranoan; Fikry Karim (Integritas: Jurnal Antikorupsi, 2026)
Village financial management, which is vulnerable to fraud, requires the implementation of more substantive accountability—going beyond mere administrative compliance. This study aims to explore why corrupt behavior persists in day-to-day administration despite extensive reforms in village financial accountability. It employs a qualitative method using a multiple-case study design at the village level in Poso Regency, Central Sulawesi. This study reveals that existing financial management regulations and audit mechanisms tend to foster symbolic accountability. Administrative-based financial reporting, oversight, and audits—often treated as mere compliance—are more frequently used to secure funds, mitigate the risk of audit findings, and maintain political legitimacy rather than to strengthen public oversight. On the other hand, citizen participation has been reduced to a mere formality due to restrictions on oversight imposed by complex procedures and regulations. Consequently, budget implementation report’s function more as symbols of accountability—merely fulfilling obligations—rather than as effective internal control instruments to prevent corruption. This finding further underscores that village governance with low capacity is vulnerable to symbolic accountability. Therefore, more context-specific, inclusive, and meaningful participatory mechanisms are required.